The infamous ratsos Infamous ratsos series, book 1. - LaReau, Kara. (2016)
A 2017 Theodor Seuss Geisel Honor Book! Louie and Ralphie Ratso are no softies. Readers are sure to chuckle as the determined Ratso brothers' plans to act tough go hilariously awry. Louie and Ralphie Ratso's dad, Big Lou, always says that there are two kinds of people: those who are tough and those who are soft. Louie and Ralphie are tough, tough, tough, just like Big Lou, and they're going to prove it. But every time they try to show just how tough they are, the Ratso brothers end up accidentally doing good deeds instead. What'll Big Lou do when he finds out they've been acting like softies all over the Big City? Perfect for emerging and reluctant readers, this clever and surprisingly warmhearted chapter book shows that being tough all the time can be really tough.
Text Difficulty 2 - Text Difficulty 3
LG/Lower grades (K-3rd)
620
3.5
Electronic reproduction.
Keywords: Juvenile Fiction; Humor (Fiction).; Juvenile Literature; Electronic books